THE IMPACT OF RISK TOLERANCE AND TRUST ON THE CONTINUANCE INTENTION OF MOBILE PAYMENT USAGE - Andrea, Patricia
In Indonesia, fast-growing Fintech or digital financial services, such as mobile payment services have sprung up with the continuous technological advancements. However, with so many mobile payment players in Indonesia, mobile payment companies are faced with the task of being able to maintain their current customers and raise the number of users so that they continue to be used as one of the existing payment methods. The fact is that some customers often prefer to discontinue their user activities even though they trust the mobile application, since there is no incentive or promotion from the providers. It is therefore important, apart from trust, to understand the role of benefits and risks that influence the behavior of continuing mobile payment. Risk tolerance is used because of its strength which enables the risk-benefit trade-off process in regard to the use of mobile payment. This study is therefore intended to address the gap in mobile payment post-adoption behavioral study and to add to the current literature on mobile payment by examining risk tolerance and trust on shaping a person’s continuance intention in using mobile payment. The research also tried to expand the Theory of Reasoned Action (TRA) and Technology Acceptance Model (TAM) models by adding two additional constructs, namely Risk Tolerance and Trust. This study's respondents were mobile payment users aged 15-29 in Bandung city. Construct assessment in this study uses a Likert scale, and the PLS-SEM approach is used for data analysis. The results showed that Risk Tolerance and Trust influence Continuance Intention using mobile payment. The Risk Tolerance variable affects Continuance Intention directly, but the Trust variable does not significantly affect Continuance Intention. The research is supposed to be beneficial for practitioners and scholars to support the strategy and the references in relevant fields.